Digitalisasi Sistem Penjualan pada UD Sumber Agung untuk Meningkatkan Efisiensi Operasional - Adryan Surya Susila; Istian Kriya Almanfaluti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
MSMEs play a vital role in the economy, yet many still face challenges due to manual business management. UD Sumber Agung, a B2C and B2B cracker-selling MSMEs, experienced challenges in transaction recording, stock management, and financial reporting, resulting in inaccurate data and suboptimal decision-making. This community service activity aimed to assist and empower partners through the implementation of a smart cashier application to support business digitization. The implementation method included needs identification, system implementation assistance, application usage training, and outcome evaluation. The results demonstrated increased operational efficiency through automated and real-time recording, neater and more accurate reporting, and increased partner capacity in utilizing digital technology.